Stock Market Integration: An International Perspective - Dorodnykh, Ekaterina; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book provides an original approach to the determinants of stock exchange integration. With case studies of successful integration projects in Europe, North America, Latin America as well as intercontinental cross-border mergers, it provides a complete analysis of all existing integration projects between stock exchange markets.
Keywords: Science; Science; Science, general